Simultaneous repair of pectus excavatum and pulmonary valve implantation years after complete repair of tetralogy of Fallot - Tuncer, Eylem; Vuran, Ali Can; Özyüksel, Arda; Yeğinsu, Ali; Ceyran, Hakan (Springer Japan KK, 2017)
Although pectus excavatum is a common congenital abnormality of the chest wall, its coexistence with congenital heart defects is rarely encountered. In this report, we present a young adult who was re-operated for pulmonary valve regurgitation and pectus excavatum years after complete repair of tetralogy of Fallot. The surgical challenge and pitfalls are discussed along with a brief review of the literature.
WOS: 000394220800010
PubMed ID: 26232358
Keywords: Pectus Excavatum; Tetralogy of Fallot; Congenital Heart Disease; Pulmonary Valve Insufficiency